PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN - Tania Ivanna A. Tanto; Aaron M. A. Simanjuntak; Bill J.C Pangayow (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2019)
The value of the company is very important because the high value of the company will be followed by the high prosperity of shareholders. The higher the stock price, the higher the value of the company, in order to achieve company value, investors generally give their management to professionals. Optimizing company value can be achieved through the implementation of financial management functions, where one financial decision taken will influence other financial decisions and have an impact on the value of the company. This study aims to determine the effect of investment decisions, funding decision taken will influence other financial decision and have an impact on the value of the company. This study aims to determine the effect of investment decisions, funding decisions and dividend policies on firm value. The population in this study are all companies listed on the Indonesia Stock Exchange for the period 2014-2016 while sample selection using purposive sampling technique obtained 89 companies that will be used as samples in this study. The hypothesis testing uses multiple regression analysis. The results of the study partially show that investment decision affect the value of the company, funding decisions do not affect the value of the company and dividend policy does not affect the value of the company. While the simultaneous research resultshows that investment decisions, funding decisions and dividend policies have a significant effect on firm value